SISTEM PENJUALAN DEPOT AIR MINUM BERBASIS WEBSITE - ismi, ismiditari; Raja Joko Musridho; Deddy Gusman (Universitas Pahlawan Tuanku Tambusai, 2024)
A sales system is a system that involves resources within an organization, procedures, data, and supporting facilities to operate the sales system, thus providing useful information for management in decision making. Drinking water depot is a business sector that sells drinking water in gallon bottles. Apart from being easy to obtain and practical, the price of gallon refill water is relatively cheaper and can be consumed directly by the public. The information system for selling refillable drinking water in Bangkinang City has not been managed well, therefore, a website-based drinking water depot sales system is needed. The aim of this research is to provide convenience when ordering refill drinking water, refill drinking water transactions and preparing sales results reports. designing a website-based gallon water sales information system. The method used in system development is the waterfall method. The result of this research is a gallon water sales information system built using PHP and the Laravel Framework, designed using UML, and tested using the Blackbox Testing method.